Six Years Experience With Porcine Extracellular Matrix: A New Paradigm for Pelvic Floor Repair [1G]. Issue 1 (May 2017) - Storey, Jean; Yordan-Jovet, Raul; Kambiss, Scott
Abstract : INTRODUCTION: Retrospective case series report on the efficacy and safety of using the porcine extracellular matrix Matristem® (ACell, Columbia, MD) in the surgical management of pelvic organ prolapse (POP). METHODS: Charts of patients treated surgically for POP with a porcine bladder graft at our institution between 2010 and 2015 were reviewed. Pre and postoperative POP-Q scores were compared. Surgical complications and adverse events were surveilled. RESULTS: 84 patients were identified with POP including 93 pelvic reconstructive procedures performed. 61 anterior repairs (AR) including 17 total vaginal hysterectomies with modified McCall's uterosacral ligament cuff suspensions, and 6 concurrent posterior repairs (PR). 27 additional posterior repairs, 2 vaginal para vaginal repairs (VPVR), and 3 bilateral sacrospinous ligament colpopexies (SSLC). Preoperative POP-Q scores measuring level 1 and level 2 support ranged from -2 to +6. POP-Q scores obtained 3 to 72 months (median = 54) postoperatively revealed durable global level 1 and 2 support with most at -3 scores. 2 anatomical failures to anterior or apical -1 scores, but only 1 symptomatic case needed reoperation. No significant surgical or product complications were identified. CONCLUSION: Secondary to procurement inconsistencies associated with synthetic and cadaveric products, and the risk of erosion, fibrosis, retraction, or dyspareunia with synthetic materials, our preliminary data shows that Matristem xenografts offers a safe and efficacious alternative in the surgical repair of level 1 and 2 POP.